1998
DOI: 10.1046/j.1365-2141.1998.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell chronic lymphocytic leukaemia with CD8 expression: report of 10 cases and immunochemical analysis of the CD8 antigen

Abstract: We report 10 cases of B-cell chronic lymphocytic leukaemia (B-CLL) with expression of the T-cell antigen CD8. The majority of patients had typical B-cell CLL with stable and non-progressive stage A(O) disease except for more common expression of lambda light chain and CD25. Two patients had progressive disease and required therapy, one with atypical morphological and phenotypic features. The incidence of CD8 expression was approximately 0.5% of B-CLL patients from our institutions. Immunoprecipitation of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 21 publications
3
34
3
Order By: Relevance
“…Some reports suggested that CD8 expression was associated with a favorable prognosis either in terms of lack of progression or good response to treatment [4][5][6][7][8][9][10][11][12]; however, other reports suggested CD8 as a marker of aggressive disease [13,14]. Our patient showed an indolent clinical course.…”
Section: Discussioncontrasting
confidence: 37%
See 4 more Smart Citations
“…Some reports suggested that CD8 expression was associated with a favorable prognosis either in terms of lack of progression or good response to treatment [4][5][6][7][8][9][10][11][12]; however, other reports suggested CD8 as a marker of aggressive disease [13,14]. Our patient showed an indolent clinical course.…”
Section: Discussioncontrasting
confidence: 37%
“…The cytoplasmic domain of CD8 recruits the T-cell specific tyrosine kinase, p56lck, to the TCR-CD8-MHC signalling complex triggering downstream signalling for T-cell activation [16]. A previous study showed that p56lck was absent in three of four cases of CD8+ CLL, suggesting a non-functional CD8 in CLL cells [9]. In our patient, the CLL population clearly expressed CD8, but lacked the T-lineage defining antigens of CD3 and CD7.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations